2019
DOI: 10.1007/s40858-019-00307-x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of orthotospovirus populations and dispersion under different environmental conditions in Brazil and in the Dominican Republic

Abstract: Orthotospoviruses (genus Orthotospovirus, family Tospoviridae) are amongst the most devastating plant viruses worldwide, causing severe damage to many economically important vegetable crops, such as tomato and sweet pepper. Monitoring virus populations is an important step for estimating virus damage and epidemiology, and gaining insights into the adaptation processes undergone by orthotospoviruses. Here, we studied the orthotospovirus populations infecting vegetable crops in Brazil and the Dominican Republic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
2
0
1
Order By: Relevance
“…This pattern was also found by Martínez et al. (2019), in a study that analysed the TCSV and GRSV populations in Brazil and the Dominican Republic.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This pattern was also found by Martínez et al. (2019), in a study that analysed the TCSV and GRSV populations in Brazil and the Dominican Republic.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, the complete sequence of the TCSV M segment (isolate RDS31) revealed that it was equally similar to that of isolates SA-05 of GRSV and BR-03 of TCSV, thus corroborating the results obtained by Silva et al (2019), where both isolates were compared and it was revealed that they share the same M segment, thereby concluding that TCSV may have incorporated the GRSV M segment through a reassortment event. This pattern was also found by Martínez et al (2019), in a study that analysed the TCSV and GRSV populations in Brazil and the Dominican Republic.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Vinculado con lo anterior, se comprobó que algunas de las nuevas especies, corresponden a eventos naturales de reordenamiento, en los que, virus muy relacionados intercambian información genética aumentando su diversidad (Qiu et al, 1998;Martínez et al, 2019) y formaría parte de una adaptación evolutiva a huéspedes, vectores y zonas geográficas (Tsompana et al, 2005;Tentchev et al, 2011). Eso explicaría por qué el genoma de algunos aislados de TCSV está compuesto por los segmentos L y S de GRSV y uno M propio, que a su vez tiene alta homología con el correspondiente de GRSV (Qiu et al, 1998;Webster et al, 2011;de Breuil et al, 2016).…”
Section: Organismos Causalesunclassified